Does the shape of the electric pulse matter in electroporation? - Novickij, Vitalij; Rembiałkowska, Nina; Szlasa, Wojciech; Kulbacka, Julita (Frontiers in Oncology, 2022)
Electric pulses are widely used in biology, medicine, industry, and food processing. Numerous studies indicate that electroporation (EP) is a pulse-dependent process, and the electric pulse shape and duration strongly determine permeabilization efficacy. EP protocols are precisely planned in terms of the size and charge of the molecules, which will be delivered to the cell. In reversible and irreversible EP applications, rectangular or sine, polar or bipolar pulses are commonly used. The usage of pulses of the asymmetric shape is still limited to high voltage and low voltage (HV/LV) sequences in the context of gene delivery, while EP-based applications of ultra-short asymmetric pulses are just starting to emerge. This review emphasizes the importance and role of the pulse shape for membrane permeabilization by EP.